Synthesis, physico-chemical characterization and biological activity of 2-aminobenzimidazole complexes with different metal ions - Podunavac-Kuzmanović Sanja O.; Cvetković Dragoljub M.; Vojinović Ljiljana S. (Acta Periodica Technologica, 2004)
Complexes of 2-aminobenzimidazole (L) with nitrates of cobalt(II) nickel(II), copper (II), zinc(II) and silver(I) were synthesized. The molar ratio metal:ligand in the reaction of the complex formation was 1:2. It should be noticed, that the reaction of all the metal salts yielded bis(ligand) complexes of the general formula M(L)2(NO3)2 × nH2O (M=Co, Ni Cu, Zn or Ag; n=0, 1, 2 or 6). The complexes were characterized by elemental analysis of the metal, molar conductivity, magnetic susceptibility measurements and IR spectra. Co(II), Ni(II) and Cu(II) complexes behave as non-electrolytes, whilst Zn(II) and Ag(I) are 1:1 electrolytes. Cu(II) complex has a square-planar stereochemistry, Ag(I) complex is linear, whilst the Co(II), Ni(II) and Zn(II) complexes have a tetrahedral configuration. In all the complexes ligand is coordinated by participation of the pyridine nitrogen of the benzimidazole ring. The antimicrobial activity of the ligand and its complexes against Pseudomonas aeruginosa, Bacillus sp. Staphylococcus aureus and Saccharomyces cerevisiae was investigated. The effect of metal on the ligand antimicrobial activity is discussed.